(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Objective: The aim of this study was to explore the outcome of surgical removal of endometriotic cyst on ovarian reserve. Materials and methods: This prospective observational study was carried out in Infertility Care and Research Centre, Dhaka, Bangladesh between January 2011 and December 2018. One hundred and fifty-five patients, who had an ultrasonographic diagnosis of endometrioma measuring ³3 cm and underwent surgical excision due to subfertility were the candidates for this study. The exclusion criteria were a) previous ovarian cystectomy, b) removal of one ovary, c) irregular menstrual cycle, d) polycystic ovarian syndrome e) endocrine disorder, f) low AMH (<1ng/ml), g) history of taking medication for endometriosis that could affect ovarian function, e.g., GnRH analogues or oral contraceptives during the 6 months preceding scheduled surgery. To investigate the effect of surgery on ovarian reserve, their FSH, E2 and AMH were measured before and after surgery. Tests were done before surgery and repeated after 3 months and 6 months of surgery. A value of < 0.05 was considered significant. Results: Mean age of the patients was 31.72 ±2.77 years. The baseline FSH, E2 and AMH were within normal limit. In 63.88% of the cases the cysts were unilateral and 83.22% of the cases the size of the cysts were within 10 cm. To assess the change of ovarian reserve FSH, E2 and AMH were measured in 3 and 6 months after surgery. There was marked declining of AMH level from baseline to both 3 months and 6 months after surgery p is <0.0001. There was no significant change of FSH and AMH between 3 months and 6 months after surgery. Conclusion: Cystectomy in ovarian endometrioma significantly reduces ovarian reserve, which is menifested by reduced level of AMH. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 96-101